2021
DOI: 10.1186/s12877-020-01856-6
|View full text |Cite
|
Sign up to set email alerts
|

Associations between objectively measured physical activity, sedentary behaviour and time in bed among 75+ community-dwelling Danish older adults

Abstract: Background Older adults are recommended to sleep 7–8 h/day. Time in bed (TIB) differs from sleep duration and includes also the time of lying in bed without sleeping. Long TIB (≥9 h) are associated with self-reported sedentary behavior, but the association between objectively measured physical activity, sedentary behavior and TIB is unknown. Methods This study was based on cross-sectional analysis of the Healthy Ageing Network of Competence (HANC S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In this study, the sum of Count values was calculated from the acceleration data in 1-minute segments to calculate the PA. Based on the PA value, sedentary as well as the low-, medium-, and high-intensity activity ( 6 , 23 ) can be classified. Specifically, the vertical axis acceleration signal was resampled to 30 Hz, and the acceleration values within a certain range were converted to the corresponding Count values in a sequence of 30 sample points and according to a threshold setting ( 24 ). A period of data longer than 90 min with PA kept at 0 was detected as a non-wear time and screened out ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the sum of Count values was calculated from the acceleration data in 1-minute segments to calculate the PA. Based on the PA value, sedentary as well as the low-, medium-, and high-intensity activity ( 6 , 23 ) can be classified. Specifically, the vertical axis acceleration signal was resampled to 30 Hz, and the acceleration values within a certain range were converted to the corresponding Count values in a sequence of 30 sample points and according to a threshold setting ( 24 ). A period of data longer than 90 min with PA kept at 0 was detected as a non-wear time and screened out ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several methodological aspects also need to be highlighted. First, we used proportions of waking window rather than absolute durations in physical behaviours or light exposure to address their dependency with sleep time resulting from the finite nature of the 24-hour day duration [17,23,24]. Second, we assessed day-to-day association of physical behaviours and light with sleep instead of average data over several days.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Some other studies, but not all [19], found weekly average physical activity to be associated with better sleep quality [20][21][22][23], with stronger evidence for light-intensity than moderate physical activity [20,21]. Several studies have also reported that longer sedentary time might be deleterious for sleep duration [24] and quality [19,25] although the strength of the association varies between studies. Given the potential importance of physical behaviours (sedentary behaviour (SB), light-intensity physical activity (LIPA), and moderate-to-vigorous physical activity (MVPA)) for sleep, it is important to consider the full spectrum of activity intensities [19,21,24].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations